Neuronal changes induced by proprioceptive and strength training - Gollhofer, A. (2004)
Proprioceptive Training: Stretch-Reflex-Activation and Explosive Strength Mechanisms: Enhanced reflex-drive facilitates MN-pool - enhanced fusimotor control - withdrawal of presynaptic inhibition Function: Earlier access in voluntary and in reflexive contraction conditions